Women Movement in Modern Pakistan Found in Novel “I Am Malala” - Sri Lestrawati Tampubolon; Robby Satria Mandala (Humanitatis : Journal of Language and Literature, 2021)
This study discusses the bad conditions experienced by women in Pakistan and their actions to fight for these conditions in the modern era as seen in the novel "I Am Malala" by Malala Yousafzai and Christina Lamb. The method used in this study is a qualitative descriptive method. In analyzing the data, the researcher used descriptive analysis and informal methods in presenting the research results. In this study, the author applies the theory of liberal feminism from Mary Wollstonecraft which makes literary works as a reflection of society. The researcher analyzes and provides an overview of Malala's life then the author relates it to the theory. The method used to analyze the data in this study is a qualitative research method, where the researcher conducts research on a literary work by describing it based on the facts (data) which is then followed by analysis with the aim of getting an overview of the aims and objectives of the study. The data source for this analysis is the novel I Am Malala itself. From the results of the analysis, it was found that women have liberal feminism in education, work and work, which is shown by Malala to have the opportunity to have freedom of choice.